Integration of Remotely Sensed Digital Elevation Model Data and Geographic Information System Facilities to Estimate Net Solar Radiation Variances in Iraq (1987-2017) - Homadi, Mustafa E.; Jawad, Laith A. (Iraqi Journal of Science, 2021)
The calculation of potential earth’s surface solar radiation is imperative for analyzing the atmosphere-vegetation-soil interaction process. Therefore, many schemes were introduced with direct (using net radiometer) or indirect (using air temperature or air plus soil temperatures) formulas. Three combinations of factors are known to control the Rn value; the astronomical based factors which determine the general spatial distribution of Rn values, the climatological factors which determine the assigned spatial variation of those values, and the topographical factors that influence climatological factors rates ( i.e. have indirect effects on Rn values). For Iraq, the ecosystem influences of global warming were obvious in the 1980s and the Rn rates approached peak values .. Thereafter, the general behavior of Rn rates was geographically-based , i.e. increasing rates in the middle and southern regions and descending rates in the northern parts, since it was spatially correlated in a reverse manner with RH values. In the present study, this issue was clarified by utilizing the standard annual mean Rn rate known for Iraqâ€™s weather, which was 9.8MJ.m-2.year-1. The results showed that, in 1987, the area with annual mean Rn equal or higher than this annual standard rate was 305088.098 km2. The area was reduced to 241984.77 km2 in 1997, followed by an expansion to 294491.136 km2 in 2007, and another reduction to 277272.542 km2 in 2017.